The implementation of the global navigation satellite system (GNSS) in Nigeria: the challenges - Dodo, Joe D.; Kamarudin, Md. Nor (2007)
The Global Navigation Satellite Systems (GNSS) is extremely valuable tool across a broad range of applications, creating opportunities for regional and international technological advances in the areas of positioning and location-based services, surveying and mapping, disaster management, air, land and sea navigation, food security and emergency response. GNSS technology provides opportunity for developing countries to take advantage of applications that improves the quality of life, social and economic progress and support priorities for sustainable development. Whereas the developed countries has fully recognized and taken advantage of this technology, the developing countries like Nigeria is woefully underutilizing it to the detriment of her economic and social development. Despite the launch of a communication satellite (NigComSat-1) by the Nigerian government carrying two L-band payload for GNSS augmentation purposes, there is no good government policies towards the establishment of GNSS technology, human resource development, public and private sensitization and participation for the effective utilization of GNSS technology. This paper highlights some of the challenges facing Nigeria towards the realization of GNSS technology and proposes a framework for the implementation of GNSS in Nigeria.